The impact of population growth on economic growth and poverty reduction in Uganda - Stephan Klasen; David Lawson (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2007)
The paper examines the link between population and per capita economic growth, and poverty, using the interesting case study of Uganda. Although Uganda has recently experienced excellent economic growth and poverty reduction, it currently has one of the highest population growth rates in the world which, due to the inherent demographic momentum, will persist for some time to come. By combining both a macro and microeconometric approach, using panel data, we are able to consider the impact of population growth on per capita economic growth and poverty. We find both theoretical considerations and strong empirical evidence suggest that the currently high population growth puts a considerable break on per capita growth prospects in Uganda. Moreover, it contributes significantly to low achievement in poverty reduction and is associated with households being persistently poor and moving into poverty. This is therefore likely to make substantial improvements in poverty reduction, and per capita growth, very difficult.
Keywords: O15; I32; J13; 330; population; poverty; Uganda; household size; Bevölkerungswachstum; Sozialprodukt; Wirtschaftswachstum; Armut; Bevölkerungsökonomie; Uganda